2022
DOI: 10.1101/2022.09.20.508571
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Dispersal provides trophic-level dependent insurance against a heatwave in freshwater ecosystems

Abstract: Climate change-related heatwaves are major recent threats to biodiversity and ecosystem functioning. However, our current understanding of the mechanisms governing community resilience (resistance and recovery) to extreme temperature events is still rudimentary. The spatial insurance hypothesis postulates that diverse regional species pools can buffer ecosystem functioning against local disturbances through immigration of better adapted taxa. However, experimental evidence for such predictions from multi-troph… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 89 publications
(113 reference statements)
0
1
0
Order By: Relevance
“…The future study of both resistance and resilience of aquatic communities to warming would help to characterize more sensitive organismal groups and, consequently, possible functional losses. Future research should investigate these responses of aquatic communities across a wider range of experimental temperatures, including the heatwave periods (Vad et al, 2022 ). The microbial communities are still poorly studied groups, and our results showed that the temperature promoted the change in the identity of the microfauna species.…”
Section: Discussionmentioning
confidence: 99%
“…The future study of both resistance and resilience of aquatic communities to warming would help to characterize more sensitive organismal groups and, consequently, possible functional losses. Future research should investigate these responses of aquatic communities across a wider range of experimental temperatures, including the heatwave periods (Vad et al, 2022 ). The microbial communities are still poorly studied groups, and our results showed that the temperature promoted the change in the identity of the microfauna species.…”
Section: Discussionmentioning
confidence: 99%